JAVANESE TRANSLATION OF ANÂ ALLÂH: STUDY ON THE JAVANESE TRANSLATION IN QS. THAHA/20:9-15 - Fauzan, Aris; Wibowo, Safrudin Edi; Muhsin, Masrukhin; Rohmansyah, Rohmansyah; Ismail, Nawari (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
The purpose of this article is to reveal the Javanese translation of the word Anâ Allâh in QS. Taha/20: 9-15. To discuss the issue the author uses a critical content analysis and comparative analysis approach. The findings in this qualitative research are: first, the translators agreed to use Ingsun to translate Anâ Allâh. Second, they use Ingsun for Anâ Allâh because they want to dwell and honor Allah above everything, the Almighty. It is related to their understanding, awareness, and implementation of Javanese culture, unggah-ungguh (honorific speech). Third, they chose Ingsun to translate Anâ Allâh: philosophically, Ingsun is the Essence and Existence of God. Culturally ethically, Ingsun is only used by high-class people. An ordinary man who pronouns Ingsun for himself, shows that he is involved in conflict or doesn’t understand unggah-ungguh. Sufistically, Ingsun is a perfect word that represents a person's spiritual experience of uniting with his God. This research significantly contributes to the body of knowledge on ethical linguistics in religious texts, especially from a Javanese perspective which is relatively understudied by scholars of Islamic studies.